(untitled) (Research, Society and Development, 2020)
In dairy cattle farming there are different breeding systems, which can influence the thermal comfort of the animals. The cattle, in turn, have mechanisms of thermal regulation to maintain homeostasis and a zone of thermoneutrality. However, these animals have significant sensitivity to solar radiation and have thermoneutral zones with lower temperatures than most Brazilian regions. This fact has had a great impact on the dairy economy due to the negative effects on the welfare, production, reproduction and behavioral changes of dairy cows, in addition to affecting the entire production chain, from gestation, growth of calves and reproduction of males. Thus, the present bibliographic review aims to analyze the effects of thermal stress on the different aspects of dairy cattle, showing how harmful it can be.